250 students and teachers from Vocational Colleges KV participate in the TVET PRS Empowerment Programme - Nor Salwana, Mohammad Idris (UMPSA, 2023)
PEKAN, August 7, 2023 - The organization of the TVET Empowerment Programme with Peer Facilitators (PRS), which involved a total of 250 students and teachers from 86 Vocational Colleges (KV) throughout Malaysia, successfully ignited interest, developed potential, and empowered the competitiveness of students in TVET-related fields.